Certification of stone fruit crops in Ukraine - Triapitsyna, N.; Udovychenko, K.; Vasyuta, S. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
The results are the work during 2004—2018 years in Ukraine on the selection of material of stone fruits crops, which satisfies the requirements of the normative international documents for the creation of a prebasic clones collection. Analyzed state of plant material certification of these cultures.